Pelatihan Managemen Kelas dengan Pendekatan Behavioral Bagi Guru SDN 1 Plalangan Kecamatan Jenangan, Kabupaten Ponorogo - Ivayuni Listiani; Melik Budiarti; Fauzatul Ma’rufah Rohmanurmeta (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Service activities are carried out to increase the knowledge and skills of elementary school teachers in class management so that teachers can handle or manage classes according to their needs and create classes that are conducive to the teaching and learning process. The method of implementing service activities is carried out through 3 stages, namely lectures, demonstrations, and applications. The lecture method is carried out to provide an overview and knowledge for the teacher in managing the class, the demonstration method is carried out by providing examples of implementing classroom management through a behavioral approach, and the application is carried out by directly applying classroom management with a behavioral approach. The activity was carried out at SDN 1 Plalangan Ponorogo, Jenangan District, Ponorogo Regency with as many as 10 teachers participating in the training, the training activities were carried out for 2 days with a duration of 5 hours each day. Based on the results of the activities that have been carried out, it can be concluded that the teacher understands better managing the class and is able to apply class management properly according to the material that has been given so that class conditions become conducive and improve the quality of student learning.